Educational Governance in a Globalized World: Comparative Perspectives on Accountability, Autonomy, and School Performance - Michael Turner; David K (PT Mutiara Bustan Ilmu, 2025)
This study examines how educational governance operates within an increasingly globalized world, focusing on comparative perspectives of accountability, autonomy, and school performance across different national contexts. Globalization has reshaped governance frameworks by introducing international standards, cross-national policy borrowing, and performance-based accountability systems that influence national reforms. Despite extensive global discourse on school governance, significant gaps remain in understanding how varying degrees of school autonomy interact with accountability pressures to affect institutional quality and student outcomes. Using a comparative qualitative approach, this research analyzes governance models in multiple countries representing centralized, decentralized, and hybrid systems. Findings reveal that high-autonomy systems require robust accountability mechanisms to ensure equity, while highly centralized systems often struggle with innovation and responsiveness to local needs. The study highlights that effective governance depends not merely on autonomy or accountability alone, but on balanced alignment between policy design, leadership capacity, and socio-cultural conditions. These insights contribute to global education policy debates and provide practical considerations for countries seeking to enhance school performance through improved governance structures.